The States Foreign Investment Diplomacy Challenges - Leila Raeisi (Dulat/pizhūhī, 2017)
Today states have a vast network of international relations and have thus far managed to establish comprehensive mechanisms in some sectors of their relations. However, in the realm of foreign investment they have failed to establish such universal framework. In this regard, main questions are: whether negotiation can lead to a universal agreement as to the conclusion of a universal treaty on foreign investment? What are the main challenges and obstacles facing this path? Generally speaking, if these negotiations are conducted in a systematic and harmonious manner along with clear definition of fundamental concepts as well as determination of the sensitive issues, then one could hope to be moving toward the said objective. However, the challenges and obstacles facing this path should not be neglected; several issues such as cultural and ideological differences, the atmosphere of negotiations, bureaucracy, differences in monetary currencies, all constitute examples of such challenges. Nevertheless, a general framework which can embrace the conflicting interests of states can lead to the conclusion of a universal treaty on foreign investment. In this respect, ensuring an acceptable transparency in the pre-negotiation stage and during the negotiations could eliminate the ambiguities which might exist in fundamental issues facing the foreign investment and will, therefore, help states proceed towards establishment of a universal mechanism for coordinating the system which governs worldwide investment and hence, further improvement in international economy.